PENGEMBANGAN SMART INFRASTRUCTURE PADA ASPEK PRASARANA PERKOTAAN DI KOTA BANDARLAMPUNG - Diah Mayang Sari; Muhammad Zainal Ibad; Adinda Sekar Tanjung (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
The city of Bandar Lampung, which is the capital of Lampung Province, which is currently not included in the 100 smart city movement in Indonesia, has tried to keep up with and make Bandar Lampung a smart city. Marked by the vision of the City of Bandar Lampung, namely "Bandar Lampung is healthy, intelligent, faithful, cultured, superior and competitive based on the people's economy" (RPJMD Bandar Lampung City, 2016-2021). The increasing number of residents in Bandar Lampung City causes basic infrastructure services to be improved in order to meet the needs of the community. The concept of smart infrastructure that has been implemented in various countries has been able to help fulfill and maximize city infrastructure services to be effective and efficient. Research on smart infrastructure in Bandar Lampung City is still new and relatively early, so it is very important to know the position of smart infrastructure development in Bandar Lampung City. This development can be identified by examining the stages of the city's smart infrastructure (Royal Academy of Engineering, 2017 in Ogie et al, 2019). The purpose of this study is to examine the development of smart infrastructure in urban infrastructure aspects in Bandar Lampung City. This research was conducted using a qualitative deductive approach, while the research data were analyzed using content analysis techniques and qualitative descriptive analysis. The result of this research is that the urban infrastructure of Bandar Lampung City is at an early stage towards the concept of smart infrastructure, which is still between the traditional stage and the semi-intelligent stage.